Anti-Hepatitis B Antibody Levels In Immunized Medical Students: Are They At Risk? - Keila Zaniboni Siqueira Batista; Lucas Pecker de Azambuja; Suzane de Souza; Maely Cordeiro de Souza; Caio Maurício Mendes de Cordova; Hercílio Higino da Silva Filho (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Abstract INTRODUCTION Medical students have an occupational risk for hepatitis B (HB). This study sought to determine anti-HBs and anti-HBc IgG levels in vaccinated students, check their seroconversion, and correlate this with vaccination. METHODS One hundred and forty-three students’ blood samples and their vaccination schedules were analyzed. RESULTS: 65.7% were positive for anti-HBs; however, anti-HBs was absent in 34.3%. Only two samples were positive for anti-HBc IgG. CONCLUSIONS More than 30% of students did not have minimum protective levels. Comparing HBV vaccination and anti-HBs reactivity, the majority of reactive individuals received their last dose within the past 16 years.